2015
DOI: 10.1111/aas.12515
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of leukocyte CD11b and CD64 expression in severe sepsis and non‐infectious critical care patients

Abstract: Neutrophil CD64 as well as neutrophil and monocyte CD11b expressions were highest in severe sepsis compared with non-infectious conditions, and thus analyses of their expression may be promising approach for sepsis diagnosis in ICU population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…CD11b has been shown to have rapid up- and down-regulation depending on the activator. 17 , 34 , 35 Lack of upregulation of neutrophil CD11b, CD162, CD15s, and CD65s in otherwise activated neutrophils can be a sign of immune dysfunction in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…CD11b has been shown to have rapid up- and down-regulation depending on the activator. 17 , 34 , 35 Lack of upregulation of neutrophil CD11b, CD162, CD15s, and CD65s in otherwise activated neutrophils can be a sign of immune dysfunction in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Also, CD11b/CD18 (Mac-1) is a β2 integrin known as a pro-inflammatory molecule that promotes phagocyte cytotoxic function and enhances the function of several effector molecules [ 21 ]. A recent study showed that CD11b expression in neutrophils and monocytes was elevated in severe sepsis versus non-infectious conditions [ 22 ]. However, some studies have reported that Mac-1 plays significant immunoregulatory roles, and variations of the ITGAM gene, which encodes the CD11b chain, are a strong genetic risk factor in SLE [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD64 expression in neutrophils was measured using quantitative flow cytometry as previously described. 10 Key agents used in the assay included anti-CD64-FITC and CD45-PC5 antibodies (FC500; Beckman Coulter, Brea, CA, USA). The neutrophil CD64 index was calculated as the mean CD64 fluorescence intensity in neutrophils divided by the mean CD64 fluorescence intensity in lymphocytes.…”
Section: Methodsmentioning
confidence: 99%